A EMERGÊNCIA DE DIFERENTES ÁREAS DO SABER NAS PESQUISAS SOBRE LINGUAGEM - Guedes, Marymarcia (Intercâmbio, 2010)
In spite of the conveyed reality remains the same, the difficulties of translation from language one to language two result from the fact that the conceptual mapping is different in distinct languages. Similarly the linguistic field researches are related to other knowledge areas - mainly the Anthropology - trying to find in it the theoretical support in order to understand to communicative processes wich happen within a society.